Agile Transformation: A Case Study on Early Stage of Agile Adoption - Helmlinger, Peter (Naše gospodarstvo/Our economy, 2023)
Agile transformation is identified as a facilitator to keep pace with frequent changes within product development. Although initial research exists, the empirical literature on the implementation process of the agile approach, specifically using pilot projects as a change strategy, is scarce. The purpose of this article is to contribute to closing this gap by investigating into effects of piloting agile change projects. To shed light on agile pilots a project within the context of mechatronic system development in the high-tech industry was accompanied over six months. After the initiation of the members and a period of practicing agile a survey was performed. The interviewed team members are bringing up interesting findings, as although they had a different understanding of agile at the beginning of the pilot, they recognized agile values, principles and methods as supportive to the products cycle and specifically development time. Further findings are indicating that professional third-party support is a key success factor. Also piloting, as a change strategy for agile adoption, is proven to be supportive. Although piloting is proven a supportive strategy, the downsides, such as limited scalability caused by extraordinary setups, are identified and analyzed. The limiting factor of this single-case study is the small sample size of data due to the intention of the pilot project to limit impact and risk on the organization.